Effects of Neoadjuvant Chemotherapy in High-Grade Non-Metastatic Osteosarcoma of Extremities - Samardziski, Milan; Janevska, Vesna; Zafirova-Ivanovska, Beti; Vasilevska, Violeta; Kraleva, Slavica (IntechOpen, 2012)
None